(untitled) (Research, Society and Development, 2022)
The production of hybrid fish is a practice that has been used in Brazil. Aiming at the best performance of hybrid species, fish farms are increasingly exploring this technique. In some regions of Brazil, the hybrid “pintado da Amazônia” or “jundiara” has been produced on a large scale, obtained from the cross between a female cachara (Pseudoplatystoma punctifer) and a male Amazon catfish (Learius marmoratus). However, researches that prove the zootechnical advantage of these crosses over the pure parental species are scarce and insufficient, and more work is needed on the morphology, behavior and performance of this hybrid. The objective of the present study is to survey the pathogens on the Branchiura parasite in the different stages of the production of the hybrid “pintado da Amazônia”. The analysis was carried out on a property in the State of Rondônia, in the municipality of Santa Luzia, line P26, km 20, the study analyzed aspects related to fattening, captive management, sanitary and physiological aspects of the Amazonian painted, and also, the changes in the environment that provide conditions in which ectoparasites Branchiura (Argulidae) multiply, which may increase the occurrence of disease in the Amazonian Pintado. Despite the zootechnical advantages, the fattening of the Amazonian Pintado should be monitored, and further studies should be carried out on its performance, morphology and the environmental impact caused by the inclusion of this specimen in nature. Future comparisons of these data with the pure parental species will be of vital importance in evaluating the advantages and disadvantages of growing this hybrid in Brazil.